Management and Support Systems of Guidance in Elementary Schools - Jenimis Oktapiani; Ana Puspita Sari (EDOVA JOURNAL : Education for Nation Development Journal, 2025)
This study aims to examine and analyze the management of the guidance system at SDN 27 Olo Ladang, as well as to identify the factors influencing the effectiveness of its implementation. This research uses a qualitative approach with a case study method. Data were collected through observation, interviews, and documentation. The findings reveal that the management of the guidance system in elementary schools still faces various challenges, including unstructured planning, lack of standardized implementation guidelines, limited facilities and professional counseling personnel, infrequent program evaluation, and low parental involvement in the guidance process. The guidance programs tend to be reactive and are not designed based on students’ developmental needs. Based on these findings, improvements are needed in planning, teacher training, provision of supporting facilities, regular program evaluation, and strengthening parental involvement. Enhancing these aspects is expected to make the guidance system more effective in supporting students' academic, social, and emotional development in elementary schools.